Discrete logarithm problem in matrix - Povilas Tvarijonas; Gediminas Simonas Dosinas; Eligijus Sakalauskas (Lietuvos Matematikos Rinkinys)
In this paper the discrete logarithm problem in matrix in finite fields is formulated, possible ways of solution are given.